Comparative Effect on the Utilization of Moringa Oleifera Seed Meal in Local and Exotic Chickens - Adeyinka Oye Akintunde; Ayokunle Afolabi Toye; Abimbola Alice Ademola (Syiah Kuala University, 2021)
The study aimed at determining the nutrigenetic effect of Moringa oleifera (MOSM) on obesity, liver and kidney function parameter of broilers and local chicken. Moringa oleifera has been found to have anti-inflammatory and antipyretic properties. A total of 96 broiler chickens and 96 local chickens were randomly assigned to 4 dietary treatment groups. Each group contained 24 birds (8 birds per replicate in 3 replicates) each for both genotypes of chicken in a factorial layout within a completely randomized design such that birds in each genotype were randomly allocated to four diets (control diet contained 0% MOSM and 5%, 10% and 15% graded levels of MOSM as diets 2, 3 and 4 respectively). Obesity was determined through weekly measurement of body weight and body mass index (BMI). Serum total cholesterol, kidney and liver functioning parameters were determined at week 8 by analyzing for creatinine, ALT, AST and ALP. Broilers exhibited higher creatinine, total cholesterol, ALT, AST and ALP but no significant difference (P0.05). Broilers exhibited significantly higher (p0.05) BMI than YENLC. G* Ed interactions were observed at age 8 weeks. MOSM resulted in significantly higher (P0.05) BMI in birds fed 10% MOSM at week 8. Increasing levels of MOSM also yielded reduction in the level of total cholesterol for both genotypes. There was no significant (P0.05) interaction between genotype and MOSM utilization by the chickens and BMI at week 8, cholesterol, creatinine, ALT, AST and ALP. Thus, dietary intervention through the inclusion of MOSM is effective in lowering heart disease risk through lowering of adiposity (BMI) and cholesterolaemia and it has little or no toxic effect as AST and ALP were not significantly affected.